Search of Astrophysical results with LIGO from the Science runs S1 to S5 - Naseer, Iqbal; SHOWKAT, MONGA; Zahir, Shah (JOURNAL OF ADVANCES IN PHYSICS, 2014)
The gravitational wave detectors especially LIGO has attained its design sensitivity and up gradation has virtually reached near the completion. The gravitational wave search is in progress and hopefully result will be possible in due course of time. We discuss the recent attempts to detect various classes of signals which include un-modelled sub second burst of gravitational radiation like from core collapse supernoval and Î³-ray burst engine. A stochastic background of gravitational waves of cosmological origin would provide a new idea about early universe. We discuss current attempts to detect gravitational waves from these sources and know about future prospectus of these searches.